Technologies for producing Plant Biostimulants using Cold Plasma and Low-Pressure Microwave Discharge - Kocira, Slawomir (2024)
In recent years, it has been realized that agriculture has become one of the economic sectors with a huge impact on the environment. Therefore, measures have been taken to reduce the negative impact of agricultural production on the environment. The use of biostimulants in agriculture, especially of plant origin, is part of this trend. However, obtaining suitable formulation of biostimulants requires the development of appropriate technologies for their production. Therefore, it was undertaken to investigate the possibility of using gliding arc cold plasma (GA) and low-pressure microwave (MW) discharges to produce water plant extracts with biostimulating potential. An increase in total polyphenol content and antioxidant activity was observed, indicating the high potential of using low-pressure microwave discharge to produce effective plant biostimulants. Also, low-pressure microwave discharge improved the extraction of elements such as Ca, K and Fe.